Breast cancer prevention in women treated at Primary Care Unit - Raquel Leda de Arruda; Edvane Dias Teles; Natália Silva Machado; Francisca Jacinta Feitoza de Oliveira; Iolanda Graepp Fontoura; Adriana Gomes Nogueira Ferreira (Universidade Federal do Ceará, 2015)
Objective: to describe the profile of women treated at Primary Care Unit and identify the attitudes toward early detection of breast cancer. Methods: exploratory and descriptive research conducted with 40 women aged over 20 years, after nursing consultation. Results: it was verified that a share of participants presented risk factors for breast cancer, especially menarche before age 12, 57% (n=23); no breast examination during the consultation, 70% (n=28); and never have done breast examination, 57.5% (n=23). As for performing the self-examination, 80% (n=32) of women said they knew how to do it, of which 65.5% reported performing it monthly, 12.5% ​​never did it, and 23% of women over 40 years did not undergo mammography. Conclusion: we highlight the need to develop effective educational interventions addressing the risk factors and early detection of breast cancer in the health services.